2004
DOI: 10.1207/s15327078in0603_4
|View full text |Cite
|
Sign up to set email alerts
|

14‐Month‐Old Infants Form Novel Word—Spatial Relation Associations

Abstract: This study explored 14-month-old infants' ability to form novel word-spatial relation associations. During habituation, infants heard 1 novel word (e.g., teek) while viewing dynamic containment events (i.e., Big Bird placed in a box) and, on other habituation trials, a second novel word (e.g., blick) while viewing dynamic support events (i.e., Big Bird placed on the box). Each novel word was presented in a sentence (e.g., "She's putting Big Bird teek the box"). During the test, infants discriminated an event t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 16 publications
3
12
1
Order By: Relevance
“…Our results are consistent with prior studies demonstrating that between 7 and 17 months, infants begin to discriminate, categorize, and attend to path or manner (Casasola et al, 2003;Pruden et al, 2004;Pulverman & Golinkoff, 2004;Pulverman et al, 2008) and are beginning to associate novel forms with actions (Casasola & Cohen, 2000;Casasola & Wilbourn, 2004). Moreover, our findings add to the growing body of research demonstrating infants' ability to attend to iambic stress in a variety of tasks.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results are consistent with prior studies demonstrating that between 7 and 17 months, infants begin to discriminate, categorize, and attend to path or manner (Casasola et al, 2003;Pruden et al, 2004;Pulverman & Golinkoff, 2004;Pulverman et al, 2008) and are beginning to associate novel forms with actions (Casasola & Cohen, 2000;Casasola & Wilbourn, 2004). Moreover, our findings add to the growing body of research demonstrating infants' ability to attend to iambic stress in a variety of tasks.…”
Section: Discussionsupporting
confidence: 90%
“…Future research should investigate how stress might help with other types of verbs, such as manner, and also whether this associative ability is evident at younger ages. We chose 16 months because we know that between 14 and 17 months, English-learning infants attend to both manner and path in nonlinguistic tasks (Pulverman et al, 2008), and around this age, infants are developing the ability to associate novel labels with actions (Casasola & Cohen, 2000;Casasola & Wilbourn, 2004). It may be the case that salient linguistic information such as word stress facilitates this mapping at even younger ages.…”
Section: Discussionmentioning
confidence: 99%
“…Second, previous studies demonstrated that 6‐month‐old infants discriminate a containment relation from other relations on the basis of the relation and not on the basis of the figure's occlusion (Casasola et al, 2003). Likewise, 14‐month‐old infants tested on their ability to link a novel word to a containment relation or a support relation discriminated between the relations from different angles, including a high angle in which there was no difference in the occlusion amount of the figure in the containment and support events (Casasola & Wilbourn, in press). Together, these findings strongly suggest that infants in the current study were responding to the spatial relation and were not responding solely on the basis of simple perceptual cues.…”
Section: Discussionmentioning
confidence: 99%
“…Children could accomplish this separation in part by detecting the function morphemes and meanings characteristic of each category (Gerken & McIntosh, 1993;Maratsos, 1982;Mintz, 2002;Waxman & Booth, 2003). Santelmann and Jusczyk (1998) reported that 18-month-olds detect the dependency between is and -ing in verb phrases; children also begin to learn spatial prepositions early in the second year (Casasola & Wilbourn, 2004;Meints, Plunkett, Harris, & Dimmock, 2002). Such findings reveal hints of the morphological and semantic knowledge relevant to disentangling verbs from prepositions.…”
Section: Consequences For Syntactic Bootstrappingmentioning
confidence: 99%